TOLERANSI MASAM Vitex pubescens VAHL. IN -VITRO DAN EX-VITRO - Asri Insiana Putri (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
This study aims to observe acid tolerance of Vitex pubescens culture growth. Planlet cultures were established from seeds on Murashige & Skoog medium supplemented with 1 µM benzylaminopurin; 0,1 µM kinetin and 0,01 µM naphtalenaceticacid. The pH was adjusted to 5,7;4,0 and 3,0. The mean height of planet were 4,44 cm ± 0,32 for pH 5,7; 2,88 cm ± 0,54 for pH 4 and 1,10 cm ± 1,38 for pH 3. The mean length of root were 13,72 cm ± 0,47 for pH 5,7; 18,88 cm ± 0,60 for pH and 19,27 cm ± 0,73 pH 3. The mean number of branch roots per cm were 1,65 ± 0,058 for pH 5,7;3,88 ± 0,18 for pH 4 and 0,57 ± 0,30 for pH. After 12 weeks acclimatization in Yellow Red Podzolic (YRP) soil, the mean height of plant with pH 5,7 culture were 29,86 cm ± 0,64 and 26,72 cm ± 0,40 for pH culture. In vitro acid tolerance of Vitex pubescens were at pH 4 and can grow in ex vitro condition in YRP soil with pH 4,48.